Fecal Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-Cov-2) RNA Is Associated With Decreased Coronavirus Disease 2019 (COVID-19) Survival. (10th July 2021) - Das Adhikari, Upasana; Eng, George; Farcasanu, Mara; Avena, Laura E; Choudhary, Manish C; Triant, Virginia A; Flagg, Meaghan; Schiff, Abigail E; Gomez, Isabella; Froehle, Leah M; Diefenbach, Thomas J; Ronsard, Larance; et al.
Abstract: The clinical significance of severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) RNA in stool remains uncertain. We found that extrapulmonary dissemination of infection to the gastrointestinal tract, assessed by the presence of SARS-CoV-2 RNA in stool, is associated with decreased coronavirus disease 2019 (COVID-19) survival. Measurement of SARS-CoV-2 RNA in stool may have utility for clinical risk assessment.